Pengaruh Model Problem Based Learning Terhadap Self Directed Learning Pada Pembelajaran Tematik Terpadu - Novita, Dian; Fitria, Yanti (Elementary Teacher Education Program, Majalengka University, 2023)
The examination is pointed toward making sense of the effect of the Issue Put together Learning models with respect to the Independent Learning elemenraty school understudies' on the subject 'enviroment is our closest companions'. This research is in a quantitative form with quasy experimental design. The design used is The Non Equivalent Control Group Design. The sampling technique was cluster random sampling with the population consisted of 6 SD in Cluster I Kec. Lintau Buo. The resserch was directed at SDN 09 Taluak as an exploratory class added up to 16 studens and SDN 10 Tigo Jangko as a control class added up to 15 studens. The preconditioned normality, homogeneity, and hypothetical t-test tests were the methods of data analysis utilized in the study. Pre-test avarege for the exploratory class was 46,25 and in the wake of carrying out the Issue Based Learning models, the post-test subsequent to being shown utilizing the conventional approach 64,13. The ttest yielded tcount = 3,605 and ttable = 2,045, respectively, with a significance level of 0,05. This tcount = 3,605 versus ttable = 2,045 indicates that the effect of Problem-Based Learning models on Elementary Students' Self-Directed Learning on the topic